2002
DOI: 10.1093/jn/132.4.703
|View full text |Cite
|
Sign up to set email alerts
|

Almonds and Almond Oil Have Similar Effects on Plasma Lipids and LDL Oxidation in Healthy Men and Women

Abstract: Epidemiologic and clinical studies have shown that nut consumption is associated with favorable plasma lipid profiles and reduced cardiovascular risk. These effects may result from their high monounsaturated fat (MUFA) content but nuts contain constituents other than fatty acids that might be cardioprotective. We conducted a study to compare the effects of whole-almond vs. almond oil consumption on plasma lipids and LDL oxidation in healthy men and women. Using a randomized crossover trial design, 22 normolipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
126
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(131 citation statements)
references
References 28 publications
2
126
1
2
Order By: Relevance
“…Our results are in agreement with those previously published for other tree nuts (Rajaram et al, 2001;Hyson et al, 2002) and other MUFA-rich foods (Grundy, 1986;Kris-Etherton et al, 1999a). The present study also demonstrated that a high-MUFA-rich diet had the added benefit of not increasing TAG, as the lowcholesterol diets recommended by the American Heart Association tend to do (Ginsberg et al, 1990).…”
Section: Effects Of Hazelnut-enriched Diet On Plasma Lipid Profiles Ssupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are in agreement with those previously published for other tree nuts (Rajaram et al, 2001;Hyson et al, 2002) and other MUFA-rich foods (Grundy, 1986;Kris-Etherton et al, 1999a). The present study also demonstrated that a high-MUFA-rich diet had the added benefit of not increasing TAG, as the lowcholesterol diets recommended by the American Heart Association tend to do (Ginsberg et al, 1990).…”
Section: Effects Of Hazelnut-enriched Diet On Plasma Lipid Profiles Ssupporting
confidence: 93%
“…Incorporation of hazelnut (40 g/day) into human diet favorably altered multiple plasma lipid variables in hypercholesterolemic adult men (Figure 1 and Table 5). Our results are comparable to those reported for other tree nuts such as almond (Hyson et al, 2002), macadamia (Garg et al, 2003), pecan (Rajaram et al, 2001), pistachio (Edwards et al, 1999) and walnut (Zambó n et al, 2000), despite the fact that inclusion of Effects of hazelnut-enriched diet on plasma lipid profiles SM Mercanlıgil et al hazelnut into the human diet in our study was less than half of those reported for other nuts. The intake of SFA generally increases the risk of CHD by increasing the concentrations of total and LDL cholesterol, and Apo B, and increasing the ratios of total/HDL cholesterol and LDL/HDL cholesterol (NRC, 1989).…”
Section: Effects Of Hazelnut-enriched Diet On Plasma Lipid Profiles Ssupporting
confidence: 85%
See 3 more Smart Citations